Age-related changes in gait, balance, and strength parameters: A cross-sectional study. - Asghar Rezaei; Sandesh G Bhat; Chih-Hsiu Cheng; Robert J Pignolo; Lichun Lu; Kenton R Kaufman (PLoS ONE)
Background Longevity is increasing worldwide due to improvements in healthcare and living standards. Aging is often associated with disability and multiple health concerns. To address these challenges, effective interventions are essential. This study investigated potential age-related declines in gait, balance, and strength. We also sought to assess any relationships between these three parameters and explore potential differences between women and men. Methods Healthy individuals over 50 years of age were recruited for this cross-sectional study. Upper extremity (grip) strength and lower extremity (knee) strength of the dominant side were measured. Static balance was performed on the force plate in different situations each for 30 seconds: bilateral stance with eyes open, bilateral stance with eyes closed, as well as dominant leg and non-dominant leg unilateral stance with eyes open. Gait was measured during level walking using an optical motion capture system. Additionally, the dynamic stability margin (DSM) was calculated for the level walking trials. Results The study results indicated that gait parameters were not significantly affected by age (p≥0.12), while knee and grip strength, along with several balance parameters, showed a significant decline with age. All individuals were able to maintain their bipedal balance, but their center of pressure movement increased significantly by age (p≤0.028). Z-scores were calculated to compare significant age parameters. Unipedal stance time was found to be the most affected by age compared to other contributing factors (p≤0.001). The duration of unipedal balance showed the most significant change per decade (non-dominant: -0.62 SDs; dominant: -0.53 SDs), while strength measures exhibited the lowest amount of change per decade (grip strength: -0.34 SDs; knee strength: -0.26 SDs). Sex differences were observed exclusively in strength parameters, with no discernible impact on the decline in balance parameters. Conclusions These findings suggest that the duration of unipedal stance can serve as a reliable and gender-independent measure of neuromuscular aging for both elderly male and female subjects.